Will clearer messages close the green gap? An examination of attitude formation in organic produce buying - Caterina Fox (IUBH Internationale Hochschule, 2020)
In the area of green consumption there is a gap between the environmental concern expressed by people and the actions they are prepared to take as consumers. This so-called 'green gap' phenomenon means that while consumers' environmental beliefs are stable or even intensifying, they do not necessarily behave in an eco-friendly way or buy environmentally minded products. In this study, the green gap was explored by focusing on the formation of 'green' attitudes towards organic produce. Specifically, the role of values and specific vs. general environmental beliefs was examined. Data was collected via a standardized, quantitative survey (n=278) and analyzed with the help of hierarchical multiple regression analysis. Universalism values and specific environmental beliefs emerged as predictors of positive attitudes towards organic fruit and vegetables. Thus, the use of universalism values is recommended for the segmentation of the green market. Furthermore, marketers should communicate very clearly how buying organic will benefit the environment.
Keywords: 650; Green gap; organic; consumer behavior; attitude formation; theory of planned behavior